Peterson field guide to birds of North America - Peterson, Roger Tory, 1908-1996 (Peterson field guide series., 2008)
In celebration of the centennial of Roger Tory Peterson's birth comes a historic collaboration among renowned birding experts and artists to preserve and enhance the Peterson legacy. This new book combines the Peterson Field Guide to Eastern Birds and the Peterson Field Guide to Western Birds in one volume, filled with accessible, concise information and including almost three hours of video podcasts to make bird watching even easier.